Resection of isolated distant nodal metastasis in metastatic colorectal cancer. (June 2020) - Isom, Chelsea; Idrees, Kamran; Wang, Li; Tan, Marcus; Parikh, Alexander A.; Bailey, Christina E.
Abstract: Background: Little is known regarding the role of resection in patients with colorectal cancer (CRC) who present with isolated non-regional lymph node metastasis (NRLNM). Methods: Using the Surveillance, Epidemiology and End Results database, we identified patients diagnosed with CRC and NRLNM from 2004 to 2013. Results: A total of 849 patients presented with CRC and isolated NRLNM. Of these, 90 (10.6%) underwent resection of NRLNM. Median overall survival (OS) did not differ for patients who underwent resection of NRLNM compared to those who did not (33 versus 29 months, p = 0.68). Subgroup analysis by primary tumor site, also did not demonstrate a difference in median OS. Cox proportional hazard model revealed older age (Hazard ratio [HR] 1.34, 95% Confidence Interval [CI] 1.17–1.53, p < 0.0001), higher tumor grade (HR 1.81, 95% CI 1.52–2.16, p < 0.0001), and earlier year of diagnosis (HR 1.34, 95% CI 1.17–1.53, p < 0.0001) were associated with decreased OS. There was no survival difference between those who underwent resection of NRLNM compared to those who had not (HR 0.997, p = 0.28). Conclusion: Resection of NRLNM in patients with CRC is not associated with an OS benefit. Further studies are needed to determine if there is a subset of patients who could potentially benefit from this resection strategy. Highlights: Using the SEER database, we identified patients diagnosed with CRC and nonregional lymph node metastasis (NRLNM) from 2004-2013. 849 patients presented with isolated NRLNM and of these, 90 (10.6%) underwent resection of NRLNM while the others did not. Median overall survival did not differ for patients who underwent resection of NRLNM and those all had standard of care. There was no survival difference between those who underwent resection compared to those who had not (HR 0.997, p = 0.28).